Information Search, Integration and Personalization 9th International Workshop, ISIP 2014, Kuala Lumpur, Malaysia, October 9-10, 2014, Revised Selected Papers - Kotzinos, Dimitrios; Choong, Yeow Wei; Spyratos, Nicolas; Tanaka, Yuzuru (Communications in Computer and Information Science, 2016)
This book constitutes the refereed post-proceedings of the 9th International Workshop on Information Search, Integration and Personalization, ISIP 2014, held in Kuala Lumpur, Malaysia, in October 2014. The 6 revised full papers and one invited papers presented were carefully reviewed and selected from 19 presentations. The papers are organized around the following topics: information search in large data sets (databases, digital libraries, data warehouses); comparison of different information search technologies, approaches, and algorithms; novel approaches to information search; personalized information retrieval and personalized web search; data analytics (data mining, data warehousing); integration of Web-services, knowledge bases, digital libraries; federation of smart objects. .